Characteristics of Nonunion Fractures in Patients with Antebrachial Fractures at dr. Mohamad Soewandhie General Hospital Surabaya 2021-2022: A Retrospective Study - Monica, Tasya; Sasono, Bimo; Sekarputri, Cempaka Harsa ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: Nonunion, a complication of fracture healing, can lead to patient morbidity. Contributing factors include age, gender, fracture type, multiple fractures, infection, prolonged nonsteroidal anti-inflammatory drug (NSAID) use, smoking, nutritional status, and history of chronic disease. This study aims to determine the prevalence and characteristics of nonunion antebrachial fractures at dr. Mohamad Soewandhie General Hospital Surabaya. Methods: This retrospective descriptive study involved 111 patients. Data was gathered from medical records treated at dr. Mohamad Soewandhie General Hospital Surabaya for antebrachial fracture during 2021-2022. The study protocol obtained approvals from two local ethical committees. Data included demographics, fracture characteristics, fracture type, multiple fractures, infection, NSAID use, hypertension and diabetes history, smoking habits, and nutritional status by BMI calculation. Results: This study found a 24.3% prevalence of antebrachial nonunion fractures at dr. Mohamad Soewandhie General Hospital Surabaya in 2021-2022, mostly in males (66.7%) aged 17-25 years (22.2%). Nonunion in antebrachial fractures is marked by high rates in closed (92.6%) and single fractures (92.6%). Notably, infections (22.2%), smoking (7.4%), and hypertension history (7.4%) are common contributors. Despite ideal BMI in many cases (44.4%), nonunion still occurred. Conclusions: The study conducted at Dr. Mohamad Soewandhie General Hospital in Surabaya revealed a high prevalence of antebrachial nonunion fractures at 24.3%, particularly among young males. It was found that closed, single fractures were the most common type, with infections, smoking, and a history of hypertension being significant contributing factors. Interestingly, even individuals with an ideal BMI were still at risk for nonunion.